Educational Applications to Improve Cognitive Development in Early Children: A Review of Educational Psychology - Sappaile, Baso Intang; Damayanti, Damayanti; Jumiyah, Rahmi; Fernandez, Fransisca Debby Christine; Chusyairi, Kholil (World Psychology, 2024)
Educational applications for early childhood (PAUD) are very important for growing children's cognitive abilities. Cognitive development in early childhood develops quickly and dynamically and can be influenced by many factors, such as the environment, opportunities and their own cognitive style. This research was conducted with the aim of creating educational applications that can improve the cognitive abilities of young children through various fun educational activities. Apart from that, this educational application also aims to improve creative abilities, remember and recognize the environment around them, recognize the concepts of numbers, letters, colors, and solve problems, as well as the ability to develop other cognitive abilities. The method used by researchers in researching Educational Applications to Improve Cognitive Development in Early Childhood: A Review of Educational Psychology is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. Then the results of the data acquisition will also be tested again using the SPSS application. The results of research on educational applications to improve the cognitive development of early childhood can show several things related to educational psychology, such as, experience-based learning methods can encourage children's creativity. From this research, researchers can conclude that educational applications to improve cognitive development in early childhood are very effective for use in the learning process. With the various educational applications used in learning, it is able to create a fun learning process and can provide new experiences to young children.